A Longitudinal Study of the Relationship of Adiponectin with Reproduction in Infertile Women Undergoing IVF/ICSI Treatment, and an Experimental Study in Human Granulosa Cells - Lixian Qin; Chantacha Sitticharoon; Somsin Petyim; Issarawan Keadkraichaiwat; Rungnapa Sririwichitchai; Pailin Maikaew; Malika Churintaraphan (Life, 2023)
This study investigated the roles of adiponectin in IVF treatment during Phase I (the basal stage before gonadotropin administration), Phase II (approximately 8 days after gonadotropin administration), and Phase III (on the ovum pick-up day), as well as the effects of adiponectin on CYP19A1 and the FSH receptor (FSHR) mRNA expression in a human granulosa-like tumor cell line (KGN). In human subjects (a longitudinal study, n = 30), blood samples were collected in all phases, while follicular fluid (FF) was only collected in Phase III. The participants were classified into successful and unsuccessful groups based on the determination of fetal heartbeats. KGN cells were treated with adiponectin/FSH/IGF-1 (an experimental study, n = 3). There was no difference in the adiponectin levels between successful and unsuccessful pregnancies in the FF (Phase III) and in serum (all phases), as well as among the three phases in both groups. Serum FSH (Phase I) was positively associated with serum adiponectin in the unsuccessful group, but it had a negative association in the successful group (all phases). Serum adiponectin and serum FSH (Phase I) were positively correlated in the unsuccessful group, whereas they were negatively correlated (all phases) in the successful group. The serum adiponectin levels (Phase III) were significantly higher than in the FF in unsuccessful pregnancies, but there was no difference in successful pregnancies. FF adiponectin concentrations were negatively correlated with serum LH in successful subjects. In KGN cells, adiponectin had no influence on CYP19A1 and FSHR mRNA expression. High adiponectin levels in serum compared to FF (Phase III) in unsuccessful subjects might negatively impact IVF treatment.